2020
DOI: 10.3390/biomedicines8110518
|View full text |Cite
|
Sign up to set email alerts
|

ACTN4 Mediates SEPT14 Mutation-Induced Sperm Head Defects

Abstract: Septins (SEPTs) are highly conserved GTP-binding proteins and the fourth component of the cytoskeleton. Polymerized SEPTs participate in the modulation of various cellular processes, such as cytokinesis, cell polarity, and membrane dynamics, through their interactions with microtubules, actin, and other cellular components. The main objective of this study was to dissect the molecular pathological mechanism of SEPT14 mutation-induced sperm head defects. To identify SEPT14 interactors, co-immunoprecipitation (c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 61 publications
0
8
0
Order By: Relevance
“…Interestingly, SEPT12 interacts with the SUNdomain-containing nuclear membrane protein SPAG4 and may Review therefore link the spermatid nucleus to microtubules 135 . SEPT14 also interacts with a-actinin-4 at the nuclear envelope and the manchette and might link both microtubules and actin to the nuclear membrane 136 . Septins have been similarly implicated in linking microtubules to the plasma membrane.…”
Section: Roles Of Microtubule-associated Septins In Cellular Morphogenesismentioning
confidence: 99%
“…Interestingly, SEPT12 interacts with the SUNdomain-containing nuclear membrane protein SPAG4 and may Review therefore link the spermatid nucleus to microtubules 135 . SEPT14 also interacts with a-actinin-4 at the nuclear envelope and the manchette and might link both microtubules and actin to the nuclear membrane 136 . Septins have been similarly implicated in linking microtubules to the plasma membrane.…”
Section: Roles Of Microtubule-associated Septins In Cellular Morphogenesismentioning
confidence: 99%
“…In our previous study, we discovered that the mutated SEPT14 resulted in teratozoospermia (n = 6), with >14% spermatozoa retaining their normal morphology [ 29 ]. We further identified SEPT14 interactors, a peptide of RAB3B/C [ 30 ]. In this study, Figure 1 and Supplementary Figure S2 suggest that RAB 3C is a major component of human sperm formation within the RAB3 family, and there is no RAB3B signal.…”
Section: Resultsmentioning
confidence: 99%
“…In our previous studies, we identified mutations in the SEPT12 and SEPT14 genes by sequencing their coding regions and showed that they caused severe sperm head deformation and DNA damage in male infertility cases [ 26 , 29 ]. We also found that SEPT12 and SEPT14 form filamentous structures and assist in sperm head shaping and tail elongation during human spermiogenesis [ 25 , 26 , 29 , 30 , 55 ]. SEPT12 or SEPT14 mutations disrupt filamentous structures, causing morphological defects in sperm and DNA damage [ 25 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Correspondingly, SEPT12 mutations have been described in infertile men displaying abnormal sperm including defective annulus with a bent tail (Kuo et al 2012). Additionally, defective sperm head morphology and DNA integrity have recently been reported for two different SEPT14 missense mutations (Wang et al 2019, Lin et al 2020). Previous findings proposed a septin ring assembly as octameric filaments at the annulus, classically composed of septins 12-7-6-2-2-6-7-12 or 12-7-6-4-4-6-7-12, in which septins 12 and 7 and septins 6 and 2/4 are connected through their GTP-binding domain (G-interface), whereas septins 7 and 6 and the two central septins 2/4 interact via their NC-termini (NC-interface) (Sirajuddin et al 2007, Kuo et al 2015).…”
Section: Discussionmentioning
confidence: 99%